KONFIGURASI POLITIK HUKUM PERTANAHAN INDONESIA DALAM PERSPEKTIF TEORI HUKUM RESPONSIF - Budi Handoyo SH.,MH (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2018)
The Constitution has mandated the provisions governing agrarian problems, namely in Article 33 paragraph (3) of the 1945 Constitution states â€œEarth and water and the natural resources contained therein are controlled by the State and used for the greatest prosperity of the peopleâ€. Number 5 of 1960 Basic Agrarian Regulations as a juridical basis for national land law. But in subsequent developments many laws and regulations that were never requested by the agrarianlaw were issued. The character of land law products is always in line with the development of political configurations though. Responsive characters emerge during democratic political configurations, while conservative characters emerge during a bureaucratic authoritarian political configuration. To realize democratic political configuration characterized by a responsive legal product, the Government and the legislative body must inevitably pay attention to and implement the implicit values contained in regulations and policies.